2023
DOI: 10.2147/jhc.s385478
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 Radioembolization as the Major Treatment of Hepatocellular Carcinoma

Abstract: Background The purpose of this study was to assess the safety and efficacy of Yttrium-90 radioembolization using in unresectable hepatocellular carcinoma. Methods From 2017 to 2021, 32 patients with unresectable hepatocellular carcinoma, with mean tumor diameter about 7cm (21 males, 11 females; median age, 57.5 years of age), treated with Yttrium-90 radioembolization using resin microspheres were reviewed at pre-Yttrium-90 and post-Yttrium-90 follow-up. Tumor response w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The estimated survival rate in our whole patient cohort was 82.0% and 60.5% at 6 and 12 months after TARE, respectively, which is similar to other studies evaluating patients with unresectable HCC, also regarding the proportion of patients who underwent LT after bridging TARE [ 11 , 23 , 24 ]. Despite our hospital being a specialized liver transplantation center, only approx.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The estimated survival rate in our whole patient cohort was 82.0% and 60.5% at 6 and 12 months after TARE, respectively, which is similar to other studies evaluating patients with unresectable HCC, also regarding the proportion of patients who underwent LT after bridging TARE [ 11 , 23 , 24 ]. Despite our hospital being a specialized liver transplantation center, only approx.…”
Section: Discussionsupporting
confidence: 88%
“…In this context, a bridging therapy, such as transarterial radioembolization (TARE) before liver transplantation (LT), is applied. The effectiveness of locoregional, neoadjuvant therapies for this purpose has been demonstrated by several studies [ 5 , 6 , 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Studies directly comparing TARE with TACE found a higher disease control rate, significantly better overall and intrahepatic PFS, and better survival outcomes in the patients treated with TARE even with advanced disease [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many clinical trials currently looking at this question (NCT05809869, NCT03889093, NCT05701488, NCT04605731), with some preliminary results suggesting that the combination of Y90-RE with systemic therapy can be safe and effective. 25 26 As this field of Y90-RE continues to evolve, the authors recommend strongly considering the utilization of personalized dosimetry and the limiting of the treatment angiosome whenever combination therapy with Y90-RE is sought. Of note, the combination of atezolizumab and bevacizumab has become first-line systemic therapy for advanced HCC.…”
Section: Dosimetry Fundamentalsmentioning
confidence: 99%
“…In this study, overall survival was 17.7- and 18.6-months survival, respectively. Y-90 has been shown to be effective in large tumors >5 cm, with 59% overall survival at 12 months and 60% PFS at 12 months [34]. Advances in imaging techniques and radiologic oncology have allowed more precise locoregional therapies than were previously available.…”
Section: Downstaging To Transplantmentioning
confidence: 99%